Marketing and Campaign Management via Social Networks and the Effects of Electronic Advertising (Global Journal of Management and Business Research, 2018)
This paper aims to show that the marketing and management of advertising campaigns have contributed in a positive and growing way since the nineties until now bring in targeted customers and increase sales of electronic products. Social communication networks are transformed into the promoting and marketing advertising forum in order to automatically attract customers without the need for traditional sales methods. In this sense, electronic marketing represents the space of commercial transactions of the future. Therefore, this type of marketing and the management of campaigns promoting social media via social networks have a direct impact on internet users by the effect of electronic advertising.
Keywords: electronic marketing; social media; campaign management; promotion; electronic advertising